Total paeony glycoside alleviates brain injury of rat models developed by cerebral ischemia-reperfusion - PENG Yingjuan, LI Zhiying, SUN Linlin, YANG Huijie, WANG Tiantian, ZHOU Liping (Jichu yixue yu linchuang)
Objective To investigate the effect of total paeony glycoside (TPG) on cerebral ischemia-reperfusion injury (CI/RI) of rats. Methods The rats were randomly divided into sham surgery (sham) group, CI/RI model group (simple CI/RI group), positive control group (nimodipine group, 5 mg/kg), low-dose TPG group (TPG-L group, 27 mg/kg), a high-dose TPG group (TPG-H group, 54 mg/kg)and a high-dose TPG+NOD-like receptor thermal protein domain associated protein 3 (NLRP3) activator diethyl dithiocarbamate (DDC) group (TPG-H+DDC group, 54 mg/kg TPG and 30 mg/kg DDC), with 18 rats in each, administered once a day for 7 consecutive days. After the administration, the neurological deficit score of the rats was evaluated. Nissl staining microscopy was applied to observe neuronal activity in brain tissue. 2,3,5-triphenyltetrazolium chloride (TTC) staining microscopy was applied to detect the area of cerebral infarction in rats. The level of interleukin-1β and IL-18 in brain tissue was measured by ELISA method. Western blot was applied to detect the expression of purinergic receptor P2X ligand-gated ion channel 7 (P2X7R)/NLRP3 signaling pathway related proteins and pyroptosis related proteins such as apoptosis associated speck like protein containing a CARD (ASC) and cysteine protease 1 (caspase-1) proteins in brain tissue. Results Compared with the sham group, the neurological deficit score, infarct area, level of IL-1β and IL-18 in brain tissue and protein expression of P2X7R, NLRP3, ASC, and caspase-1 in brain tissue of rats in the simple CI/RI group were significantly increased (P＜0.05), while the proportion of Nissl body positive cells in brain tissue was significantly reduced (P＜0.05). The change in corresponding indicators of rats in the nimodipine group, TPG-L group, and TPG-H group was opposite to those in the simple CI/RI group (P＜0.05). NLRP3 activator DDC antagonized the inhibitory effect of TPG on cell pyroptosis in CI/RI rats. Conclusions TPG may inhibit brain injury in CI/RI rats by down-regulating the P2X7R/NLRP3 pathway.